2012
DOI: 10.1016/j.clim.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Alternative activation in systemic juvenile idiopathic arthritis monocytes

Abstract: Systemic juvenile idiopathic arthritis (SJIA) is a chronic autoinflammatory condition. The association with macrophage activation syndrome, and the therapeutic efficacy of inhibiting monocyte-derived cytokines, has implicated these cells in SJIA pathogenesis. To characterize the activation state (classical/M1 versus alternative/M2) of SJIA monocytes, we immunophenotyped monocytes using several approaches. Monocyte transcripts were analyzed by microarray and quantitative PCR. Surface proteins were measured at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 67 publications
7
56
1
Order By: Relevance
“…However, monocytes from sJIA patients, irrespective of disease state, expressed significantly higher levels of CD16 and CD14 than healthy controls. This finding was replicated in a subsequent study which assessed the polarization state of the monocyte populations in sJIA patients with quiescent and active disease, respectively [24]. CD16 is believed to be expressed by monocytes or macrophages which have a more inflammatory M1 phenotype while CD14 is upregulated on monocytes which appear to have a more anti-inflammatory M2 gene expression profile [27].…”
Section: Cellular Biomarkers In Sjiamentioning
confidence: 79%
See 1 more Smart Citation
“…However, monocytes from sJIA patients, irrespective of disease state, expressed significantly higher levels of CD16 and CD14 than healthy controls. This finding was replicated in a subsequent study which assessed the polarization state of the monocyte populations in sJIA patients with quiescent and active disease, respectively [24]. CD16 is believed to be expressed by monocytes or macrophages which have a more inflammatory M1 phenotype while CD14 is upregulated on monocytes which appear to have a more anti-inflammatory M2 gene expression profile [27].…”
Section: Cellular Biomarkers In Sjiamentioning
confidence: 79%
“…Macaubas et al [23;24] provided recent reports on lymphocyte subsets comprising monocytes, dendritic cells, NK cells, α/β and γ/δT cells, and B cells in quiescent and active disease stages in sJIA patients. The authors reported that the relative abundance of T and B cells amongst the mononuclear cells appears lower in flaring sJIA patients compared to age-matched healthy controls.…”
Section: Cellular Biomarkers In Sjiamentioning
confidence: 99%
“…The activation of anti-inflammatory mechanisms is also supported by the M2-polarization of macrophages from patients with sJIA [39,86,88]. Contrary to classically activated macrophages (M1) that are highly proinflammatory, M2 macrophages are intended to resolve inflammation, perform scavenger functions, and promote tissue repair.…”
Section: The Defective Immunoregulation Hypothesismentioning
confidence: 99%
“…In summary, we have shown that rTsP53 functions as a modulator of macrophage polarization, and possesses potential anti-inflammatory and protective activity on early-stage sepsis induced by LPS. The M1/M2 balance has been showed to take part in multiple clinical settings such as inflammatory bowel disease, cardiovascular disease and autoimmune disease, [32][33][34] suggesting that rTsP53 has therapeutic potential for sepsis and other inflammatory diseases through the modulation of macrophages. It has to be noted that although the pro-inflammatory response of sepsis is generally the major cause of organ failure, the later anti-inflammatory stages, also described as chronic immune paralysis, cause substantial sepsis-related death.…”
Section: Discussionmentioning
confidence: 99%